Losing spring [large type] - Andrews, V. C. (Virginia C.) (Andrews, V. C. (Virginia C.). Sutherland series, 2024)
"Caroline Bryer is the daughter of a very conservative TSA agent and former military brat, Morgan Bryer. Her mother, Linsey Bryer, is a descendent of the Sutherland real estate family. Their organized, suburban life in Colonie, New York, is rigorously regulated and leaves little room for deviation from the norm. When Linsey, Morgan, and Caroline attend the wake of their neighbor Mr. Gleeson, they meet his charming daughter Natalie "Nattie" Gleeson, who works for the American ambassador to France. Linsey and Nattie strike up a fast friendship as women of a similar age in very different places in their lives -- Linsey a devoted mother and housewife, and Nattie an international diplomat living an independent and freewheeling life. Their friendship soon evolves into a romance, leading to the collapse of Linsey's marriage and her disinheritance from the Sutherland family fortune. ... a whirlwind of unexpected death, family estrangement, and a forbidden inheritance become Caroline's new reality as she struggles to navigate the loss of her mother, the mind-boggling wealth of the Sutherland family (who quickly lock her away from the world), and the loss of contact with her father following the divorce."--